Greengrocer.com.au E-commerce in action - Video Education Australasia; Image Link (Australia : Video Education Australasia, 2010)
This program examines successful Australian ecommerce business Greengrocer.com.au. This company delivers fresh fruit and vegetables to customers in Melbourne and Sydney ordered via the Internet. It describes Greengrocer's operation; how did the business start?; and what are the advantages and disadvantages of e-commerce for this type of business
Title from title screen
DVD format
Keywords: Business enterprises -- Computer networks; Electronic commerce -- Australia; Internet marketing -- Australia